التعريف بكتاب منهاج الوصول إلى علم الأصول للقاضي البيضاوي - Saepulloh, Aep; Rifqil Furqan, Muhammad (Al-Zahra : Journal for Islamic and Arabic Studies, 2023)
The research aims to get acquainted with the book “Minhaj Al-Wushûl Ilâ ‘Ilm Al- Ushûl” by Al-Qadi Al-Baydawi more closely, and its author, and the importance of the book, and the books that were written on it. The inductive, descriptive and analytical approach, as the researcher uses the comparison between the available references related to the subject and the information presented to him. The most important findings of this research is that the book Minhâj Al Wushûl is one of the most important abbreviations and al-mutûn in the ‘Ilm Ushul Al Fiqh (Fundamentals of jurisprudence), and it has many books written on this book, including the many explanations (syurûh) which number up to forty-four explanations.